pH Metric Studies on the Mixed Ligand Complexes of Ruthenium(III) with DL-2-Amino-3-Hydroxy Butanoic Acid and Nitrilotriacetic Acid in Aqueous Media - Agarwal, Vishakha; Saxena, K.K. (Asian Journal of Chemistry, 2010)
The stability constants of the mixed ligand complexes of ruthenium(III) with DL-2-amino-3-hydroxy butanoic acid (DL-threonine) as secondary ligand and nitrilotriacetic acid (NTA) as primary ligand have been determined by employing well known Irving- Rossotti method as modified by Chidambaram and Bhattacharya under varying conditions of temperature and ionic strength. It has also been found that values of stability constants for Ru(III)DL- 2-amino-3-hydroxy butanoic acid-nitrilotriacetic acid mixed ligand metal complex is significantly less as compared to the first formation constant value for Ru(III)-DL-2-amino-3-hydroxy butanoic acid binary metal complex which has been explained on the basis of factors involving properties like coulombic interaction between various ligand anion species present and steric hindrance caused by the bulky NTA molecule. Thermodynamic parameters have also been evaluated.